A review of early sport specialization in relation to the development of a young athlete - Normand, J. M.; Wolfe, A.; Peak, K. (International Journal of Kinesiology & Sports Science, 2017)
The overall physical and psychological development of a young athlete is crucial for the enjoyment of physical activity for a lifetime. Children, as well as parents, tend to focus on individual accomplishment in sport despite any other aspect of physical development or appropriate training. Objective: the pressure to excel in sport has all too often brought about negative consequences through specialization at an early age. Method: A review and commentary report on the impact of early sport specialization on the physical and psychological development of a young athlete. Conclusion: A long-term, activity and age-appropriate developmental model is essential to those involved in training young athletes. Sport specialization may be appropriate in unique situations but only after the development of specific skills, abilities, and psychological maturity. As sport professionals, parents and coaches should be educated the pros/cons of early sport specialization. Ultimately, the focus on sport participation should be to increase physical activity, psychological development, and appreciation for a lifetime.